Lessons Learned from Evaluations of Citizen Science Programs - Luke Gommerman; Martha C. Monroe (EDIS, 2012)
Extension agents with an interest in increasing the scientific and environmental awareness of their constituents may find an answer through a form of participatory scientific research known as citizen science. Citizen science uses volunteers of all ages, professions, backgrounds, and skills — often across broad geographic areas — to engage non-scientists in a variety of tasks, but most commonly data collection. This 5-page fact sheet informs potential citizen science practitioners of recent evaluations of citizen science programs. Looking closely at identifying appropriate tasks for volunteers, assessing data validity, and evaluating changes in volunteers’ knowledge and attitudes can help organizers avoid common pitfalls and develop citizen science programs most likely to succeed. Written by Luke Gommerman and Martha C. Monroe, and published by the UF Department of School of Forest Resources and Conservation, May 2012.